Aplicación de itil como herramienta para la gestión de servicios de tecnologías de información de la empresa PALMAS DEL SHANUSI – 2014 - 2015 - Huamán Olórtegui, Luis Enrique (2015)
The management of information technology in Palm Shanusi Company 2014-2015 by implementing ITIL, studies the problem of the large number of reported incidents in the area of systems, mismanagement by processes and unaware of the rules of use information technologies. ITIL is a framework of best practices, allows the management of quality IT services and suitable cost, maximize service quality, supporting the business expressly provides a clear view of the ability of the IT area, increases satisfaction at work through greater understanding of expectations and service capabilities, minimizes the cycle changes and improves the results of the processes. The population used was the staff working in Palms Shanusi Company, of a sample for the project look first the staff satisfaction survey was applied before the application of ITIL in the company Palms Shanusi the results obtained will be compared with the results of the surveys conducted after the implementation of ITIL. Applying ITIL consists in creating procedures for better management of incidents, the implementation of policies for the proper use of information technology, train staff that makes use of information technology because procedures contemplate that users will make an overhaul to your computer before you call the systems area, it is likely that the general review procedures specified in achieving solve the problem in question